Kajian Tafsir Isyari, Ayat Nafs Dalam Tafsir Al-Tustari (Al-Fajr/89:27, Al-Qiyamah/75:2, Dan Yusuf/12:53) - Iman, Khoirul; Basori (Syams, 2025)
Al-Tustari interprets the concept of soul (nafs) in the Islamic tradition with an esoteric approach, referring to three main categories namely, an-Nafs al-Mutmainnah (calm soul), an-Nafs al-Lawwamah (regretful soul), and an-Nafs al-Ammarah (soul that drives to evil). This approach combines the literal (zahir) and inner meanings in interpreting and understanding the Qur`anic verses. This provides a deep spiritual insight into the dynamics of the human soul in its relationship with God and the world. The focus of this study lies on the importance of purifying the soul (tazkiyah an-Nafs) through controlling the passions and increasing spiritual awareness as the core teachings of the Qur`an. This isyari interpretation not only reveals the textual meaning, but also the inner dimensions of the verses that correspond to the practitioners of tasawus. This study emphasizes the relevance of the Sufi approach (isyari) in the development of tafsir studies as well as a guide to increase human spiritual closeness to God.